Utilization of Supervision in Early Childhood Education and Community Education Development Institutions for Accreditation Purposes - Eva Liana (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
National Education Standards is criteria used by educational units. Educational units that will be undergoing accreditation must possess the standards which consists of: Content Standards, Process Standards, Graduate Competency Standards, Educators and Education Personnel Standards, Facilities and Infrastructure Standard, Management Standards, Financing Standards and Assessment Standards. The purpose of the Center for the Early Childhood Education and Community Education Development is so that the educational units in their working areas can be well accredited so that the level and quality of educational units which namely are nonformal education can compete with formal education. The method used by the researcher is Qualitative Descriptive to find out the extent to which supervision conducted by PP PAUD and Dikmas of West Java provides benefits to the educational unit to prepare accreditation documents. The type of research that will be used by the researcher is Case Study Research conducted in the city of Bogor and Cimahi. The techniques used are interviews, instruments and documentation. This research produces information that participants who participate in supervision activities in general can understand and have completed filling in accreditation documents so that the documents are submitted directly to the Accreditation Board of the Province of West Java. The conclusion of the researcher is that the supervision activities conducted by PP PAUD and Dikmas of West Java are very useful for educational units that will be applying for accreditation for their institution.